Sukses Menggapai Prestasi Akademik Melalui Self Regulated Learning - Azhar, Imam (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
To achieve a successful academic performance depends on intern and on extern factors. the factor that plays an important role in learning internally such as motivation, self-regulated learning, learning styles and multiple intelligences. Externally, something like learning enviroment, learning resources, adn learning facilities had become important factors. The essence of writing here is self-regulated learning. Self-regulated learning is not a mental ability or an academic performance skill; rather it is the self-directive process by which learners transform their mental abilities into academic skills. Learning is viewed as an activity that students do for themselves in a proactive way rather than as a covert event that happens to them in reaction to teaching. Self-regulated learning refers to self-generated thoughts, feelings, and behaviors that are oriented to attaining goals. In this cases, the learners should be self-regulated learners who analyzing task requirements, setting productive goals, and selecting, adapting or inventing strategies to achieve their objectives. These learners also monitor progress as they work thorough the task, managing intrusive emotions and waning motivation as well as adjusting strategies processed to foster success. These are the students who ask questions, take notes, and allocate their time and their resources in ways that help them to be in charge of their own learning.